Will Skyscrapers Save the Planet? Building Height Limits and Urban Greenhouse Gas Emissions - Rainald Borck (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper studies the effectiveness of building height limits as a policy to limit greenhouse gas (GHG) emissions. It shows that building height limits lead to urban sprawl and higher emissions from commuting. On the other hand, aggregate housing consumption may decrease which reduces emissions from residential energy use. A numerical model is used to show that total GHG emissions may be lower under building height restrictions, but only when they are very strict. Welfare is not concave in the strictness of building height limits, so either no limit or a very strict one might maximize welfare. The paper also studies the effect of endogenous transport technology and the urban heat island effect.
Keywords: Q50; R10; 330; greenhouse gas emissions; city structure; building height limits